The crystal structure of [(2,2′-bipyridine-k2 N,N)-bis(6-phenylpyridine-2-carboxylato-k2 N,O)cobalt(II)]-monohydrate, C36H26N4O5Co - Tai Xi-Shi; Xia Yu-Pei (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C36H26N4O5Co, monoclinic, C2/c (no. 15), a = 29.3826(17) Å, b = 10.3153(5) Å, c = 19.9407(12) Å, β = 107.263(6), V = 5771.6(6) Å3, Z = 8, R gt(F) = 0.0341, wR ref(F 2) = 0.0777, T = 200 K.